2014
DOI: 10.3168/jds.2013-7290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pasture versus confinement and marine oil supplementation on the expression of genes involved in lipid metabolism in mammary, liver, and adipose tissues of lactating dairy cows

Abstract: Research was conducted to evaluate the effects of management system (MS), marine lipid supplementation (LS), and their interaction on the relative mRNA abundance of 11 genes involved in lipid synthesis in mammary, liver, and subcutaneous adipose tissues in lactating dairy cows. These genes included those involved in FA uptake (LPL), de novo FA synthesis (ACACA, FASN), FA desaturation (SCD1, FADS1, FADS2), and transcriptional regulation of lipogenesis (SREBF1, SCAP, INSIG1, THRSP, and PPARG). Forty-eight peripa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…Similarly, in cows, the use of marine products alone or in combination with plant lipids induces a dramatic decrease in milk fat yield (up to −50%) associated with a lower expression of the genes involved in de novo synthesis, and/or long chain FA uptake, TAG synthesis and transcription factor SREBP1. Conversely, in a study using rumen‐protected FO or microalgae in cows, effects were neither observed on milk fat yield or in lipogenic gene expression, except for a decrease of SREBF1 expression (−15%). This absence of effect on milk fat yield is probably due to the protection treatment of oil that avoids any disturbances of ruminal metabolism and suggests that long‐chain PUFA had no effect on mammary gene expression.…”
Section: Effects Of Dietary Lipids On Lipid Metabolism In Dairy Ruminmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, in cows, the use of marine products alone or in combination with plant lipids induces a dramatic decrease in milk fat yield (up to −50%) associated with a lower expression of the genes involved in de novo synthesis, and/or long chain FA uptake, TAG synthesis and transcription factor SREBP1. Conversely, in a study using rumen‐protected FO or microalgae in cows, effects were neither observed on milk fat yield or in lipogenic gene expression, except for a decrease of SREBF1 expression (−15%). This absence of effect on milk fat yield is probably due to the protection treatment of oil that avoids any disturbances of ruminal metabolism and suggests that long‐chain PUFA had no effect on mammary gene expression.…”
Section: Effects Of Dietary Lipids On Lipid Metabolism In Dairy Ruminmentioning
confidence: 81%
“…Milk and fat yields in grazing cows are lower compared to those of indoors cows, suggesting a lower DMI at pasture . In contrast, grazing cows have higher milk yield than that of zero‐grazing cows due to the grass selection of the leafy and digestible parts of grass …”
Section: Effects Of Dietary Feedstuffs Rich In N‐3 Pufa On the Milk Lmentioning
confidence: 99%
“…These interactions have not been addressed directly here, with 2 exceptions. First, we provided a specific set of equations to predict milk FA profile for cows fed marine products, assuming that long-chain PUFA may affect the mammary lipogenesis (Angulo et al, 2012), mammary Δ 9 -desaturase activity (Kairenius et al, 2015) and possibly the transfer of preformed FA into the mammary gland (Vahmani et al, 2014). Second, the reduction of de novo mammary lipogenesis by duodenal total C18 FA flows or concentrations (Shingfield et al, 2010) has been partly taken into account by indexing the prediction of milk C4:0 to C14:0 on the availability of their ruminal precursors but also on the duodenal flow of total C18 FA (see below).…”
Section: Milk Total C18 Fatty Acids Cis and Trans Isomersmentioning
confidence: 99%
“…Angulo et al [4] studied effects of polyunsaturated FA from plant oils (sunflower and linseed oils) and algae on mammary gene abundance and reported that milk fat profile was associated with down-regulation of both mammary lipogenic enzyme gene abundance (SCD1 and FASN) and abundance of the regulatory element binding transcription factor (SREBF1; involved in the transcriptional regulation of lipogenesis). Vahmani et al [5] studied the effects of pasture versus housing and marine oil supplementation on abundance of genes involved in lipid metabolism in mammary tissue of lactating cows and found that mammary mRNA abundance of PPARG and FASN were lower in grazing compared with cows in confinement. That was accompanied by reduced secretion of de novo synthesized FA in milk.…”
Section: Introductionmentioning
confidence: 99%